APPLICATION OF TIKTOK "deutsch_eins" IN WRITING LEARNING USING VOM WORT ZUM SATZ ZUM TEXT FOR CLASS 12 LANGUAGE STUDENTS OF SMAN 1 GEDEG - Febriytanti, Erika Diah; Julaikah, Dwi Imroatu (LATERNE, 2025)
Writing skills are one of the most important skills in learning German. The background of this study is based on the results of interviews with German teachers at SMAN 1 Gedeg that the writing skills of grade 12 students are still lacking, due to the lack of variation in learning media. Therefore, the TikTok media 'deutsch_eins' can be an alternative learning media in German. This study aims to determine the application of the TikTok video media 'deutsch_eins' and the learning outcomes of writing skills by students of SMAN 1 Gedeg. The research method used is descriptive qualitative with data collection through observation and writing tests. The results of the study on the application of the TikTok media "deutsch_eins" showed that it had been successful and implemented very well. This is evidenced by the results of observations on the application of the TikTok video media 'deutsch_eins' which showed a percentage of implementation of 90% which is categorized as very good. The results of learning writing skills showed an average value that increased from 61.04 to 79.52 and 20 out of 25 students had completed the KKM standard. The conclusion of this study is that the TikTok Video media 'deutsch_eins' and Vom Wort zum Satzt zum Text can be used as German language learning media Keywords: German Learning , Learning outcomes, TikTok ‘deutsch_eins’, Vom Wort zum Satz zum Text, Writing skills.